Agro-ecological aspects of the plant-breeding using samples of spring vetch of Poltava State Agricultural Experimental Station collection - Колісник, І. В.; Барилко, М. Г.; Колісник, А. В. (Scientific Progress & Innovations, 2012)
The results of long-term work about fundamental study of plantbreeding and agro-ecological value of samples of spring vetch of Poltava State Agricultural Experimental Stations collection are given in the article. Sources of economic-valuable signs are distinguished. The prospects of using macro and microsymbiontes co-operation are preliminary found out. Possible ways of using both crop and some varieties of domestic selection are outlined in developing biological agricultural system elements the with the aim of improving nitric plant feeding and protection of their rootage from soil patogens negative influence.